IRootLab: a free and open-source MATLAB toolbox for vibrational biospectroscopy data analysis - Trevisan, Júlio; Angelov, Plamen P.; Scott, Andrew D.; Carmichael, Paul L.; Martin, Francis L. (Bioinformatics, 2013)
IRootLab is a free and open-source MATLAB toolbox for vibrational biospectroscopy (VBS) data analysis. It offers an object-oriented programming class library, graphical user interfaces (GUIs) and automatic MATLAB code generation. The class library contains a large number of methods, concepts and visualizations for VBS data analysis, some of which are introduced in the toolbox. The GUIs provide an interface to the class library, including a module to merge several spectral files into a dataset. Automatic code allows developers to quickly write VBS data analysis scripts and is a unique resource among tools for VBS. Documentation includes a manual, tutorials, Doxygen-generated reference and a demonstration showcase. IRootLab can handle some of the most popular file formats used in VBS. License: GNU-LGPL. Availability: Official website: http://irootlab.googlecode.com/. Contact:  juliotrevisan@gmail.com Supplementary information:  Supplementary data are available at Bioinformatics online.